Factors Promoting Edupreneurship among Students of Tertiary Institutions in Nigeria - ADEBAYO, David Obafemi; MICHAEL, Ifeoluwa Blessing (Ilorin Journal of Education, 2025)
This paper explored the factors promoting and hindering the adoption of Edupreneurship among students in tertiary institutions in Nigeria. Edupreneurship, which integrates entrepreneurial skills and mindset into the academic curriculum, is increasingly recognized as a crucial driver for economic development and innovation. The paper identified key factors that promote Edupreneurship, including curriculum integration, institutional support, government policies, industry partnerships, and student engagement. Each of these elements is critical in equipping students with the practical skills and knowledge needed to thrive as entrepreneurs. Moreover, several challenges impede the effective implementation of Edupreneurship. These include inadequate curriculum integration, insufficient institutional support, ineffective government policies, and limited collaboration between educational institutions and industries. The paper proposes comprehensive strategies to address these challenges, such as the development of specialized courses, the establishment of entrepreneurship centers, the revision of government policies, and the fostering of stronger industry partnerships. By implementing the suggested solutions, stakeholders can create a supportive environment that nurtures entrepreneurial talent, ultimately contributing to the broader economic growth and innovation ecosystem in Nigeria. This paper concludes with a call to action for educational institutions, government bodies, and industry partners to collaborate in advancing Edupreneurship, emphasizing its importance for the nation's future.